Wali Dalam Perspektif Ulama Dan Masyarakat Kampung Dalam Pagar Martapura - Muhammad Rusydi; Fakhrie Hanief; Ahmad Zainal Anbiya (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
This article examines the concept of saintliness (wali) from the perspectives of scholars and the local community in Dalam Pagar Village, Martapura, South Kalimantan. Within the context of Sufism, the notion of saintliness is an intriguing topic that requires in-depth understanding. This research utilizes a qualitative descriptive method, with a focus on fieldwork conducted in Dalam Pagar, where this phenomenon occurs. The research findings reveal that the views of scholars and the local community align with the general understanding within Sufism. They regard saintliness as a result of devoted practice of Islamic Sharia, unwavering faith, and profound piety. Furthermore, the social behaviors of the people in Pagar support this perspective. The community warmly welcomes the presence of saints or individuals considered to have the potential for saintliness, especially when there is endorsement and recognition from respected scholars or spiritual leaders. This recognition is reflected in various forms of reverence, such as pilgrimages, commemorative gatherings (haul), and the display of images or photographs of saints in their homes. However, it is important to note that the community also exercises caution regarding individuals who lack clear legitimacy as saints. This caution becomes more significant in the absence of official endorsement from recognized religious authorities. In conclusion, the concept of saintliness in Sufism significantly influences the culture of the community in Dalam Pagar Martapura. The perspectives of scholars and the behaviors of the community regarding saintliness reflect a traditional understanding rooted in faith, piety, and the practice of Islamic Sharia. Moreover, the legitimacy provided by religious authorities plays a pivotal role in solidifying someone's status as a saint in the eyes of the community.